Epidemiological Study of Occupational Accidents in Yazd Combined Cycle Power Plant in Years 1383 to 1390 - fereydoon laal; abolfazl barkhordari; AH KH; gholamhossein halvani (طب کار)
Introduction: According to the increasing growth of industries and technologies and consequently increasing accidents and occupational diseases, this study aimed to by analyzing the main causes of accidents in Yazd Combined Cycle Power Plant and finally prepared the situation to present suitable control measures.